Prognostic and Predictive Value of Liquid Biopsy-Derived Androgen Receptor Variant 7 (AR-V7) in Prostate Cancer: A Systematic Review and Meta-Analysis - Khan, Tanzila; Becker, Therese M.; Scott, Kieran F.; Descallar, Joseph; de Souza, Paul; Chua, Wei; Ma, Yafeng (Frontiers in Oncology, 2022)
Abstract: To perform a meta-analysis on the prognostic and predictive value of androgen receptor variant 7 (AR-V7) detected from liquid biopsy for patients with prostate cancer (PC), three databases, Embase, Medline and Scopus were searched up to September 2021. 37 studies were included. The effects of AR-V7 on overall survival (OS), radiographic progression-free survival (PFS) and prostate-specific antigen (PSA)-PFS were calculated with RevMan 5.3 software. AR-V7 positivity detected in liquid biopsy significantly correlates with worse OS, PFS and PSA-PFS (P <0.00001). Subgroup analysis of patients treated with androgen receptor signaling inhibitors (ARSi such as abiraterone and enzalutamide) showed a significant association of AR-V7 positivity with poorer OS, PFS and PSA-PFS. A statistically significant association with OS was also found in taxane-treated patients (P =0.04), but not for PFS (P =0.21) or PSA-PFS (P =0.93). For AR-V7 positive patients, taxane treatment has better outcomes than ARSi (P =0.01). Study quality, publication bias and sensitivity analysis were further assessed. Our data show that liquid biopsy AR-V7 is a clinically useful biomarker that is associated with poor outcomes of ARSi-treated castrate resistant PC patients and thus has the potential to guide patient management as well as to stratify patients for clinical trials. More studies on chemotherapy-treated patients are warranted.